2005
DOI: 10.1021/jp0555044
|View full text |Cite
|
Sign up to set email alerts
|

Soft-Landing of Peptides onto Self-Assembled Monolayer Surfaces

Abstract: Mass-selected peptide ions produced by electrospray ionization were deposited as ions by soft-landing (SL) onto fluorinated and hydrogenated self-assembled monolayer (FSAM and HSAM) surfaces using a Fourier transform ion cyclotron resonance mass spectrometer (FT-ICR MS) specially designed for studying collisions of large ions with surfaces. Analysis of modified surfaces was performed in situ by combining 2 keV Cs(+) secondary ion mass spectrometry with FT-ICR detection of the sputtered ions (FT-ICR-SIMS). Simi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

12
112
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 65 publications
(124 citation statements)
references
References 61 publications
12
112
0
Order By: Relevance
“…It decreases in the order FSAMՆHSAMϾCOOH-SAM. This observation is consistent with the results reported for SL of the singly protonated angiotensin III on the FSAM, HSAM, and COOH-SAM surfaces [12]. In that study the low sputtered signal obtained following SL on COOH-SAM was attributed to more efficient neutralization of ions on the surface relative to FSAM and HSAM surfaces.…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…It decreases in the order FSAMՆHSAMϾCOOH-SAM. This observation is consistent with the results reported for SL of the singly protonated angiotensin III on the FSAM, HSAM, and COOH-SAM surfaces [12]. In that study the low sputtered signal obtained following SL on COOH-SAM was attributed to more efficient neutralization of ions on the surface relative to FSAM and HSAM surfaces.…”
Section: Resultssupporting
confidence: 91%
“…It should be noted that because SL of mass-selected ions produces highly pure uniform films on substrates it is difficult to compare our results with results obtained using conventional surface preparation methods. We have conducted extensive characterization of peptide films prepared using dried droplet and electrospray deposition approaches [11,12,21] and concluded that SIMS spectra obtained for such films are strongly affected by the presence of impurities and the morphology of the samples generated during the drying process. SIMS spectra obtained from peptide films prepared using these approaches are more complex than the corresponding spectra obtained from films prepared by SL.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is known that charge retention and neutralization during the SL process show different behaviors on FSAM and bare Au surfaces [26]. These effects were examined further by landing Jacobsen's catalyst on the two surfaces.…”
Section: Resultsmentioning
confidence: 99%
“…This was demonstrated by ex situ time-of-flight (TOF)-SIMS analysis in the cases of SL on fluorinated and hydrogenated self-assembled monolayer (FSAM and HSAM, respectively) and COOH-SAM surfaces [25]. Peptide ions deposited onto these surfaces, with kinetic energies in the range 0 to 150 eV, retain at least one proton for long periods after deposition [26].…”
mentioning
confidence: 98%